Constitutionality and Constitution of the National Company Law Tribunal and the National Company Law Appellate Tribunal - Kamath, Karan (Christ University Law Journal, 2021)
Modern states, with their overwhelmingly encompassing jurisdictions, cannot rely on the traditional judiciary for expeditiousness. Hence, administrative adjudication is on the rise. The National Company Law Tribunal and the National Company Law Appellate Tribunal were introduced into company law, fifteen years ago, in 2002. The new company law legislation of 2013 acclimatized some of the suggestions made by the Supreme Court and the Madras High Court, but not all. Despite being established and functioning for a year now, the tribunals suffer from certain infirmities which should have been rectified after the judiciary had advised so. This article traces the journey of the constitution of the tribunals, examines the constitutionality of the provisions as they stand, and concludes by suggesting certain modifications to the existing legislation.